2020
DOI: 10.3991/ijet.v15i20.15433
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Reality in Geo-Education

Abstract: The paper discusses the technological capabilities of virtual reality (VR) in the field of education as a highly developed form of computer modeling. VR is con-sidered to be able to revolutionize the education field since it provides better en-gagement in learning activities than other teaching methods. In order to study the impact of VR technology on ensuring the quality of e-learning, an experiment is conducted during the Physical Geography online course. The current research in-volves 60 third-year students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Although various literature has studied the adoption of different technologies such as VR in education, few papers have aimed at teaching geospatial subjects. The authors of [33,34] tried to explore the potentialities of VR in geo-education. The authors of [33] used Google Earth VR during a physical geography course to investigate geographical objects in 3D form; their findings confirmed that VR is highly adaptable of achieving teaching purposes.…”
Section: Current State Of the Research Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various literature has studied the adoption of different technologies such as VR in education, few papers have aimed at teaching geospatial subjects. The authors of [33,34] tried to explore the potentialities of VR in geo-education. The authors of [33] used Google Earth VR during a physical geography course to investigate geographical objects in 3D form; their findings confirmed that VR is highly adaptable of achieving teaching purposes.…”
Section: Current State Of the Research Fieldmentioning
confidence: 99%
“…The authors of [33,34] tried to explore the potentialities of VR in geo-education. The authors of [33] used Google Earth VR during a physical geography course to investigate geographical objects in 3D form; their findings confirmed that VR is highly adaptable of achieving teaching purposes. The authors of [35] evaluated the spatial skills of students by using a VR application that provided mental rotation tests.…”
Section: Current State Of the Research Fieldmentioning
confidence: 99%
“…Learning center is composed of two parts: teaching tools and rich media. The virtual teaching and learning tools are mainly to digitize the traditional paper textbooks [14][15][16][17][18][19], and the rich media are sub-divided into four parts: images, texts, audios, and videos. With the help of this module, the teaching contents can be displayed for students in the forms of images, texts, audios, and videos more vividly, and it can enrich students' audiovisual experience, and inspire their interest; at the same time, this part can create virtual scenes that seamlessly connect the real scenes so that the teaching activities can be carried out in the corresponding teaching scenes to improve the teaching efficiency.…”
Section: Electronic Textbooksmentioning
confidence: 99%
“…Apart from geospatial applications, virtual environments also play an instrumental role in geo-education (Shakirova et al 2020). VR is considered one of the effective emerging technologies that can be used in STEM education.…”
Section: Applicationsmentioning
confidence: 99%